Strategi Branding Dan Manajemen Media Sosial Untuk Peningkatan Daya Saing UMKM Lokal Desa Bandarjo Ungaran Barat Kabupaten Semarang - Nor Rohmah, Ihda; Teti Safari; Marsiska Ariesta Putri; Jefri Heridiansyah; Wahyudi (Jurnal Pengabdian kepada Masyarakat STIE AKA Semarang, 2025)
This community service program aims to enhance the competitiveness of local MSMEs through branding strategies and the use of social media. In the digital era, MSME actors face challenges in building brand identity and utilizing social media as a marketing tool. This activity is carried out through training and mentoring for partner MSMEs in the assisted areas. The evaluation results show an increase in business actors' understanding of branding as well as an increase in promotional activities through social media platforms. This program makes a tangible contribution to supporting the digital transformation of MSMEs.